Development of civil literacy scale: A study of validity and reliability - Çakmak, Zafer; Taşkiran, Cengiz (Eskisehir Osmangazi University, 2020)
Civil literacy is a concept that enables individuals to act with an awareness about their own rights and responsibilities; to become active in civil life; and to express individual knowledge about the state's management process. Civil literacy is one of the skills that individuals should acquire in learning about the development and change of society because it demonstrates the effectiveness of individuals who have a voice and who can influence the functioning and development of the state especially in democratic societies. The purpose of this research is to develop a valid and reliable Civil Literacy Scale to measure levels of civil literacy demonstrated by pre-service teachers. The participant sample for the research was determined by a convenience sampling method from prospective teachers studying in the Faculty of Education at a university in Turkey. Exploratory factor analysis occurred on 242 pre-service teachers while a test-retest operation was conducted on 50 pre-service teachers and confirmatory factor analysis was performed on 231 pre-service teachers. As a result of the exploratory factor analysis, a 25-item Civil Literacy Scale emerged with a total variance value of 57.23%. The four-factor structure revealed by this analysis was confirmed by a confirmatory-factor analysis process. In the test-re-test operation, the internal consistency co-efficient was determined as.81 which is in accordance with the consistency of the scale between the first test and the re-test. According to Cronbach's Alpha reliability test (one of the reliability tests carried out for the overall and sub-dimensions of the scale) the overall scale of 25 items received a value of 0.92, which proved that the scale was highly reliable. In this context, it can be stated that a reliable and valid Civil Literacy Scale was obtained. © 2020, Eyup Artvinli.
Keywords: Civil literacy; Reliability; Scale development confirmatory factor analysis; Social sciences education; Validity